2022
DOI: 10.1186/s12931-022-02088-5
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid DNA methyltransferase3b deficiency aggravates pulmonary fibrosis by enhancing profibrotic macrophage activation

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive and severe disease characterized by excessive matrix deposition in the lungs. Macrophages play crucial roles in maintaining lung homeostasis but are also central in the pathogenesis of lung diseases like pulmonary fibrosis. Especially, macrophage polarization/activation seems to play a crucial role in pathology and epigenetic reprograming is well-known to regulate macrophage polarization. DNA methylation alterations in IPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This was associated with an increased expression of M2 genes such as Arg1, Fizz1, Pdgfa, and Mmp8. Consistently, DNMT3B deficiency in myeloid cells exacerbates pulmonary fibrosis, suggesting a protective role for DNMT3B in IPF via the regulation of macrophage polarization [109].…”
Section: Transcriptional and Epigenetic Mechanismsmentioning
confidence: 69%
“…This was associated with an increased expression of M2 genes such as Arg1, Fizz1, Pdgfa, and Mmp8. Consistently, DNMT3B deficiency in myeloid cells exacerbates pulmonary fibrosis, suggesting a protective role for DNMT3B in IPF via the regulation of macrophage polarization [109].…”
Section: Transcriptional and Epigenetic Mechanismsmentioning
confidence: 69%
“…DNMT3b is a major DNMT in de novo DNA methylation, which regulates macrophage polarization ( Yang et al, 2014 ). DNMT3b deficiency can promote IL4-and TGF-β1-induced replacement macrophage polarization in vitro , and enhance the pro-fibrotic macrophage polarization in the alveolar space during pulmonary fibrosis in vivo , thus promoting the pulmonary fibrosis process ( Qin et al, 2022 ). Recently, the increased DNMT1/DNMT3a were also found in IPF patients and Blm-treated mice lungs ( Wei et al, 2022 ).…”
Section: Roles Of Altered Dna Methylation Modifications In Ipfmentioning
confidence: 99%
“…On the contrary, another study provided different results. Qin et al found that DNMT3b ameliorates the development of bleomycin-induced pulmonary fibrosis by limiting M2 macrophage polarization [ 123 ]. In this case, DNMT3b acts as a negative regulator of M2 macrophage polarization.…”
Section: Dna Methylation In Fibrosismentioning
confidence: 99%